Potensi Objek Wisata Terhadap Perekonomian Masyarakat Di Kabupaten Nias Selatan - Derlina Laia (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
This study aims to describe how the tourism potential affects the economy of the people in South Nias Regency, and to describe what obstacles faced by the community in managing tourism objects in South Nias Regency. Data analysis used in this research is a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threts). The results of the study show that Baloho Indah Beach has the potential to be developed as a tourist attraction in Teluk Dalam District, South Nias Regency because of the many opportunities and strengths that can benefit the government, managers and the local community. The obstacle faced in managing the Baloho Indah Beach tourism object is the lack of facilities and infrastructure that are used in managing tourist objects.